PENGGUNAAN METODE INTERACTIVE PROBLEM TASK AND EXPERIMENT BERBANTUAN ALAT PERAGA UNTUK MEREMEDIASI MISONSEPSI TENTANG FLUIDA DINAMIS - Kandar Rusmanto; Stepanus Sahala Sitompul; Syukran Mursyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe aims of this research was to remediat of student’s misconceptions through the Interactive Problem Task and Experiment (P&E) method with props in fluid dynamics at SMA Negeri 1 Batu Ampar. One group pretest-posttest design was a method for this research. The population of this research was all students of SMA Negeri 1 Batu Ampar. The samples was used purposive sampling technique which the outcome is 34 students. Diagnostic test used as the instrument of this research, it’s consist of 9 multiple choice questions. Based on the data analysis, the mean percentage of student's misconception decreasing was 47,06%. McNemar statistic test result with dk = 1 and α = 5% showed > , this result showed that there was a significant change of the student’s conception. The DQM of P&E method in the remediation of misconception is 45,5% (normal category). In conclusion, the remediation of misconception through P&E method was capable to fixed student’s misconception. Keywords: fluid dynamics, Interactive Problem Task and Experiment, misconceptions, remediation.